(untitled) (Archives of Mechanics - Test, 2009)
We analyze the relation between Géry de Saxcé’s bipotentials representing non-associated constitutive laws and Fitzpatrick’s functions representing maximal monotone multifunctions. We illustrate by two examples (one linear and monotone, the other non-linear and non-monotone) the fact that Fitzpatrick’s representation coming from convex analysis provides a constructive method to discover the "best" bipotential modelling of a given Implicit Standard Material.